Comparison of stress level and coping strategy between therapeutic phases in newly diagnosed tuberculosis - Ni Putu Wulan Purnama Sari; Ayu Kurnia Endar Sari (International Journal of Public Health Science (IJPHS), 2020)
In newly diagnosed Tuberculosis (TB), the diagnosis and therapy duration may cause psychological stress requiring effective coping strategy. This study aimed to compare and analyze the differences of stress level and coping strategy between intensive and advanced phases in newly diagnosed TB. This cross-sectional study involved 16 respondents in intensive phase and 29 respondents in advanced phase (n=45), in the working area of Pacar Keling Public Health Center of Surabaya. Perceived Stress Scale (PSS) and coping strategy questionnaire were used for collecting data. Data were collected in May 2018. Independent sample t test was used in data analysis (α<0.05). Results showed that mostly moderate stress level and adaptive coping strategy were found in both phases. Overall, stress and coping were not significantly different between phases in newly diagnosed TB (p=0.259 and p=0.079 respectively), but the feeling of angry, losing control, nervous & depressed, whether things happened as wishes, talking problems to professionals, and trying new dangerous thing were differ significantly between phases (p=0.046, p=0.024, p=0.044, p=0.016, p=0.014, and p=0.005 respectively). Although stress level and coping strategy were not significantly different between therapeutic phases in newly diagnosed TB, but more attention needs to be given towards patients’ emotion, such as the feeling of angry, losing control, nervous and depressed, and patients’ wishes, especially in intensive phase.